2016
DOI: 10.1002/ceas.12043
|View full text |Cite
|
Sign up to set email alerts
|

The Supervisory Relationship: A Conceptual and Psychometric Review of Measures

Abstract: To date, a comprehensive review of supervisory relationship measures has yet to be published. In this article, the authors explore conceptualizations of the supervisory relationship, describe and critique 11 measures, provide recommendations for researchers and practitioners when selecting measures, and offer suggestions regarding future measure development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 64 publications
2
25
0
4
Order By: Relevance
“…The supervisory relationship “is key to the effectiveness of supervision” (ACES, , p. 7), and supervisors are reminded that they always should “attend to ethical and cultural concerns that impact the relationship” (ACES, , p. 8). Yet the construct of the supervisory relationship is still somewhat difficult to conceptualize, at least according to measures of the construct (Tangen & Borders, ). The supervisory relationship includes such variables as development phases, role induction processes, supervisor and supervisee variables, parallel processes, transference/countertransference issues, and multicultural considerations (Ladany & Muse‐Burke, ; Muse‐Burke, Ladany, & Deck, ).…”
Section: The Msjccmentioning
confidence: 99%
“…The supervisory relationship “is key to the effectiveness of supervision” (ACES, , p. 7), and supervisors are reminded that they always should “attend to ethical and cultural concerns that impact the relationship” (ACES, , p. 8). Yet the construct of the supervisory relationship is still somewhat difficult to conceptualize, at least according to measures of the construct (Tangen & Borders, ). The supervisory relationship includes such variables as development phases, role induction processes, supervisor and supervisee variables, parallel processes, transference/countertransference issues, and multicultural considerations (Ladany & Muse‐Burke, ; Muse‐Burke, Ladany, & Deck, ).…”
Section: The Msjccmentioning
confidence: 99%
“…This is consistent with previous research, such as by Patton and Kivlighan (1997), in which the internal consistency reliability estimates were .90 for the Rapport subscale and .77 for the Client Focus subscale. Evidence of sufficient content, convergent, and discriminant validity has been provided previously (Efstation et al, 1990; Gnilka et al, 2016) and further described in Tangen and Borders (2016). Previous studies concluded that using a single composite score is most appropriate due to high correlations between the two subscales (e.g., Gnilka et al, 2016; Patton & Kivlighan, 1997).…”
Section: Methodsmentioning
confidence: 67%
“…Shaffer and Friedlander (2017) defined supervisory style as the different approaches that supervisors use, combining their unique manner in responding to trainees. Tangen and Borders (2016) utilized three supervisory styles: attractive, interpersonally sensitive, and task-oriented. Attractive supervisory styles refer to supervisors who consider themselves 'warm, supportive, friendly, and open' (flexible).…”
Section: Supervisory Stylementioning
confidence: 99%